Experimental Study On Static And Dynamic Behavior Of Pp-Band Mesh Retrofitted Adobe Masonry Structure - Sathiparan, N.; Mayorca, P.; Meguro, K. (My University, 2010)
This paper introduces a technically feasible and economically affordable PP-band (polypropylene bands) retrofitting for low earthquake resistant masonry structures in developing countries. Results of the material tests and shaking table tests on building models show that the PP-band retrofitting technique can enhance safety of both existing and new masonry buildings even in worst case scenario of earthquake ground motion like JMA7 seismic intensity. Therefore proposed method can be one of the optimum solutions